PRAKTEK JUAL BELI ATAS TANAH DENGAN AKTA DI BAWAH TANGAN DI DESA SUKAMULYA KECAMATAN TAPUNG - Nst, Sri Rahmayana Br; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Government Regulation No. 37 of 1998 concerning the Occupational Regulation of the Land DeedMaker said that PPAT has the main duty to carry out part of land registration activities by making a deed asevidence that certain legal acts have been carried out regarding land rights or ownership rights to theapartment unit, which will be made the basis for registration of changes to land registration data caused bylegal actions which is one of the problems is the sale and purchase of land with an underhanded deed hasoccurred in Sukamulya Village, Tapung District. Therefore, the purpose of this Thesis Writing, namely: first,What is the practice of buying and selling land with a deed under the hand in Sukamulya Village, TapungDistrict; Second, Is the factor causing the practice of buying and selling land with a deed under the hand inSukamulya Village, Tapung District.This type of research can be classified in the type of empirical or sociological legal research, because inthis study the author immediately conducts research on the location or place under study in order to provide acomplete and clear picture of the problem under study. This research was conducted in Sukamulya Village,Tapung District. Data sources used, namely: primary data and secondary data. Data collection techniques inthis study with Observation, Interviews, and Literature Study.Conclusions that can be obtained from the results of the first study, Land Sale Practices with DeedUnder Hands in Sukamulya Village, Tapung Subdistrict, have become a habit in the community, even the peopledo not know that land sale and purchase must be done before PPAT officials do not enough by using theagreement letter, the land sale and purchase agreement that was known by the village head Second, the causesof the practice of buying and selling land with a deed under hand in the village of Sukamulya, Tapung subdistrict,are the people who do not understand or even ignorance of the seller or buyer of land regarding theapplicable legal provisions, on the basis of mutual trust between the seller and the buyer. rights and obligationsas sellers and buyers of land, land that is the object of sale and purchase has not been certified, does not havethe cost of transferring rights and facilitates the process of transferring rights. The author's advice is to givelocal governments an understanding of the importance of buying and selling land rights in the presence of landdeed-making officials (PPAT) and the community so that they are participatory as legal subjects, so that actionscarried out in community do not cause harm to the community itself.Keywords: Buying and selling-Deed under the PPAT-hand